Ethnical Diversity in the Pilot Cadets Education: Study at Banyuwangi Indonesian Aviation Academy - Ahmad Hariri; Parjan Parjan; Adolf A. Marantika; Ikhwanul Qiram (IJORER : International Journal of Recent Educational Research, 2022)
Pilot cadets take part in a series of education and training at an academy. Differences in the background of prospective cadets can affect the educational process and achievements achieved by the cadets. This study aims to analyze differences in the area of origin of the education and training outcomes of prospective pilot cadets. The study was conducted on 22 cadets of the Indonesian Aviation Academy Banyuwangi which were divided into 3 groups of regions of origin which generally had different levels of educational progress. The scores of the initial test results including the academic potential test, physical test and initial flight aptitude test were compared. Furthermore, comparisons were made for the initial flight aptitude test, flight aptitude test 1 and flight aptitude test 2. The results showed that education and training at the academy could improve the performance of the cadets but still resulted in achievement gaps due to their regional background. The results of the study can be used as a reference for the development of pilot education models. Further research can be done for deeper diversity or educational curriculum that is not yet optimal